Cd‐Rich Alloyed CsPb1‐xCdxBr3 Perovskite Nanorods with Tunable Blue Emission and Fermi Levels Fabricated through Crystal Phase Engineering. Issue 15 (17th June 2020) - Guo, Jie; Fu, Yuhao; Lu, Min; Zhang, Xiaoyu; Kershaw, Stephen V.; Zhang, Jia; Luo, Shulin; Li, Yanxiu; Yu, William W.; Rogach, Andrey L.; Zhang, Lijun; Bai, Xue
Abstract: One‐dimensional semiconductor nanostructures have already been used for a variety of optoelectronic applications. Metal halide perovskites have emerged in recent years as promising high‐performance optoelectronic materials, but reports on 1D nanorods (NRs) of all‐inorganic halide perovskites are still scarce. This work demonstrates a synthetic strategy toward cesium‐based inorganic perovskite NRs by exploiting composition‐controlled crystal phase engineering. It is accomplished for Cd‐rich mixed‐cation CsPb1‐ x Cd x Br3 nanocrystals, where the initial 1D hexagonal perovskite phase drives the growth of the 1D NRs, as supported by first‐principles calculations. The band gaps of the resulting NRs are tunable by varying the Cd‐content, and the highly uniform CsPb0.08 Cd0.92 Br3 NRs (with an average length of 84 nm and width of 16 nm) exhibit a true blue‐color emission centered at 460 nm, with a high quantum yield of 48%. Moreover, this work also demonstrates the tunability of the Fermi levels in the films made of CsPb1‐ x Cd x Br3 alloyed nanocrystals, where samples with highest Cd content show an increase of the electron concentration and a related increase in the conductivity. Abstract : It is shown that upon incorporation of sufficient levels of Cd 2+ cations, the isotropic 3D cubic lattice of CsPbBr3 nanocrystals gives way to a transformation to the 1D anisotropic hexagonal lattice, which allows 1D growth of alloyed CsPb1‐ x Cd x Br3 nanorods to be realized whose bandgaps can be tailored all across the blue spectral range from 2.40 eV for x = 0.10 to 2.74 eV for x = 0.96.